2016
DOI: 10.1038/srep37209
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin Receptor Kinase C Targeted Delivery of a Peptidomimetic Ligand-Photosensitizer Conjugate Induces Antitumor Immune Responses Following Photodynamic Therapy

Abstract: Tropomyosin receptor kinase C (TrkC) targeted ligand-photosensitizer construct, IYIY-diiodo-boron-dipyrromethene (IYIY-I2-BODIPY) and its scrambled counterpart YIYI-I2-BODIPY have been prepared. IYIY-I2-BODIPY binds TrkC similar to neurotrophin-3 (NT-3), and NT-3 has been reported to modulate immune responses. Moreover, it could be shown that photodynamic therapy (PDT) elevates antitumor immune responses. This prompted us to investigate the immunological impacts mediated by IYIY-I2-BODIPY in pre- and post-PDT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Increasing evidence suggests that dysregulated neurotrophin signaling plays a pivotal role in the development of cancer, including PC (14,15). A recently (17)(18)(19). Thus, neurotrophin signaling is one of the most attractive therapeutic targets in PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that dysregulated neurotrophin signaling plays a pivotal role in the development of cancer, including PC (14,15). A recently (17)(18)(19). Thus, neurotrophin signaling is one of the most attractive therapeutic targets in PC.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published Cancer Cell study found that NGF is overexpressed and promotes accelerated tumor development in PDAC cells, and therapy with a Trk inhibitor in conjunction with gemcitabine increased survival in a PC mouse model ( 16 ). Meanwhile, several clinical studies have indicated that NGF, TrkA, TrkB, TrkC and other neurotrophin signaling members are aberrantly overexpressed in PC samples compared to that in normal adjacent tissues ( 17 - 19 ). Thus, neurotrophin signaling is one of the most attractive therapeutic targets in PC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been shown that BODIPY dyes with iodine or bromine atoms covalently linked to the BODIPY core can be promising PDT PSs, as an alternative to the porphyrin-based photosensitizers (8-12,45); Nagano et al (47) firstly reported an iodinated BODIPY for 1 O 2 generation directed to PDT. In the same line, Akkaya (11)(12)(55)(56)(57)(58)(59)(60)(61), Burgess (10,46,62,63), Zhao (8,64) and O´Shea (65), among others (66)(67)(68)(69)(70)(71)(72)(73), have also studied BODIPYs with different halogen substitution patterns for the same purpose.…”
Section: Advancing In the Development Of Photosensitizers For 1 O 2 Based On Bodipymentioning
confidence: 99%
“…C. S. Kue et al also illustrated the immune-stimulatory effect of the IYIY ligand. Thus, the IYIY-I 2 -BODIPY conjugate is not only a targeted PDT agent, but also proved to execute immunomodulation and antitumor activity before photoactivation of the PS, acting as a chemotherapeutic agent [ 275 ]. In 2020, S. Y. Ng et al reported another bivalent ligand (IKIK) connected to a BODIPY, suggesting to actively target the TrkC receptor [ 276 ].…”
Section: How To Tame the Bulletmentioning
confidence: 99%